2020
DOI: 10.1021/acs.orglett.0c00173
|View full text |Cite
|
Sign up to set email alerts
|

Silylium-Ion-Promoted Ring-Opening Hydrosilylation and Disilylation of Unactivated Cyclopropanes

Abstract: A silylium-ion-promoted ring-opening hydrosilylation of unactivated cyclopropanes is reported. The reaction is facilitated by the γ-silicon effect, and the regioselectivity is influenced by various stabilizing effects on the carbenium-ion intermediates, including the β-silicon effect. The experimental observations are in accord with the computed reaction mechanism. The work also showcases the ability of silylium ions to isomerize cyclopropyl to allyl groups, and the resulting α-olefins engage in a silylium-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…Therefore,intermediates with no SiÀ Hbond available anymore could potentially still engage in the self-regeneration of silylium ions. [7,9,10] Ther eactions summarized in Scheme 3d emonstrate the feasibility of the approach. Et 3 SiH (5b)y ielded the same product 7aa as Et 2 SiH 2 (5a)d id in the reaction with 4a.I nt urn, Me 2 PhSiH (5c)underwent preferential dearylation, and EtMe 2 SiH (5d) showed that demethylation is favored over abstraction of an ethyl group.The observations are in line with those previously made.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore,intermediates with no SiÀ Hbond available anymore could potentially still engage in the self-regeneration of silylium ions. [7,9,10] Ther eactions summarized in Scheme 3d emonstrate the feasibility of the approach. Et 3 SiH (5b)y ielded the same product 7aa as Et 2 SiH 2 (5a)d id in the reaction with 4a.I nt urn, Me 2 PhSiH (5c)underwent preferential dearylation, and EtMe 2 SiH (5d) showed that demethylation is favored over abstraction of an ethyl group.The observations are in line with those previously made.…”
Section: Resultsmentioning
confidence: 98%
“…Theanalogy lies in Flemingsearly notion of silylium ions being fat protons, [5] and the result would likely be the carbenium ion 3 further stabilized by the b-silicon effect. [6] Assuming that the cyclopropane ring would not be directly opened by the silylium ion, [7] the fate of 3 would not be predictable,and we expected new chemistry to emerge.T he plan was to initiate the reactions of the VCPs 4 and dihydrosilanes 5 with catalytic amounts of trityl borate Ph 3 C + [B(C 6 F 5 ) 4 ] À ,r elying on hydride abstraction (Corey reaction [8] )a nd, as such, self-regeneration of silylium ions. [7,9,10] Thus,c arbenium ion intermediates such as 6 [11] would be captured by hydride.W echose the aryl-substituted VCPs 4 as model substrates and found several cyclic silanes (7-9)a sp roducts (Scheme 1, bottom) but no simple alkene hydrosilylation (4!10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Does the LA remain associated with reactive intermediates during catalysis, as has been demonstrated for the well‐studied, electrophilic borane B(C 6 F 5 ) 3 ? [10] This now‐archetypal LA catalyst maintains a close, polarizing interaction with the Si−H bond that induces silylium character in the substrate silane and allows rapid hydride transfer to the cationic intermediates resulting from nucleophilic attack at R 3 Si + . Or, does the LA simply initiate the catalysis through complete hydride abstraction and release of “free” silylium (generally either solvent‐ or silane‐stabilized), [11] which can itself act as a catalyst? [12] This latter behavior is typified by the addition of trityl cation, Ph 3 C + , to silanes [2a, 10a, 13] …”
Section: Introductionmentioning
confidence: 99%
“…3 On the other hand, the ringopening 1,3-functionalization reaction of simply substituted cyclopropane, such as aryl-substituted cyclopropane, has not been studied so much. Recently, ring-opening of cyclopropane by phosphine/borane frustrated Lewis pairs, 4 1,3-amino-uorination by N-F reagents, 5 1,3-oxyuorination and 1,3-diuorination by uoroiodine reagents, 6 1,3-dioxygenation by hypervalent iodine reagent, 7 oxo-amination by photoredox catalysis, 8 and 1,3-hydrosilylation by silylium-ion 9 have been successfully reported. However, the development of new ringopening 1,3-functionalization reactions of simply substituted cyclopropanes is still signicant due to the limited variety of functional groups that can be introduced.…”
mentioning
confidence: 99%